2021
DOI: 10.1002/bit.27750
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor scale‐up of Leptolyngbya sp.: Effect of light intensity and inoculum volume on photoinhibition and ‐oxidation

Abstract: The effect of light intensity and inoculum volume on the occurrence of photooxidation for Leptolyngbya sp. QUCCCM 56 was investigated, to facilitate the transition from small-scale laboratory experiments to large-scale outdoor cultivation. Indoor, the strain was capable of growing at light intensities of up to 5600 µmol photons/m 2 /s, at inoculation densities as low as 0.1 g/L (10% inoculation volume vol/vol). Levels of chlorophyll and phycocyanin showed a significant decrease within the first 24 h, indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In order to implement algal bioprocesses as part of broader resource circularity bio-economy drives, thermotolerant species are required for installations that will operate during the summer months in regions with high temperatures and light intensities ( Schipper et al, 2022 ). In addition to thermotolerance, it has been observed that productivity outdoors in summer may not match that modeled for promising strains that perform well in indoor tests due to outer factors like UV and contaminants ( Schipper et al, 2021 ). Given the myriad of other factors which can affect growth performance outdoors, extremophiles with culture conditions less prone to contamination, like the low pH favored by the Cyanidiophyceae, can be valuable for outdoor cultivation in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In order to implement algal bioprocesses as part of broader resource circularity bio-economy drives, thermotolerant species are required for installations that will operate during the summer months in regions with high temperatures and light intensities ( Schipper et al, 2022 ). In addition to thermotolerance, it has been observed that productivity outdoors in summer may not match that modeled for promising strains that perform well in indoor tests due to outer factors like UV and contaminants ( Schipper et al, 2021 ). Given the myriad of other factors which can affect growth performance outdoors, extremophiles with culture conditions less prone to contamination, like the low pH favored by the Cyanidiophyceae, can be valuable for outdoor cultivation in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the content of C-phycocyanin was lower than that of Arthrospira [32], it had a phycocyanin content similar to that of another Leptolyngbya sp. which was cultured under field conditions in a previous study (20.2 ± 0.4 mg g −1 ) [33]. Over the past few years, Arthrospira has been cultivated on a large scale as a valuable source in various industries due to its high protein content and the presence of bioactive compounds, such as C-phycocyanin and chlorophyll-a [34].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as light intensity and photoperiod (also known as light:dark cycle) are as important as the quality of light [53]. Schipper et al [72] found out in their preliminary experiments that a thermotolerant Leptolyngbya sp. strain could not grow normally at high radiations (up to 2800 µmol m −2 s −1 ) due to their lack of adaptation.…”
Section: Discussionmentioning
confidence: 99%